Potency and Utilization of Cocoa Pod Husk as an Alternative Feed for Ruminants - Puastuti, Wisri; Susana, IWR (Indonesian Bulletin of Animal and Veterinary Sciences, 2014)
Cocoa pod husk (CPH) is potential as an alternative source of feed for ruminants due to its quantity and quality. The availability of CPH in Indonesia during the harvest season is abundant and able to feed around 635,305 animal unit (AU) per year. Cocoa pod husk as a feedstuff which contains crude protein between 6.80-13.78%; NDF 55.30-73.90% and ADF 38.31-58.98% is a source of fiber and can replace grass. However, CPH also contains antinutritional compounds such as lignin, tannin and theobromine. In order to optimize the use of CPH as feed, treatments are needed to improve the nutritive value and digestibility, to reduce negative effects and to extend shelf life. Processing methods can be conducted physically, chemically and microbiologically. Processing can improve the nutritional value of CPH especially the protein content. Feeding livestock using processed CPH showed better weight gain than that of unprocessed CPH. Besides, the attempt to utilize CPH as feed can overcome the shortage of forage, especially during dry season and increase ruminant productivity around the area of cocoa plantations. Key words: Cocoa pod husk, alternative feed, processing, ruminant